Colleges and schools-College of Arts and Humanities-Theatre Arts and Dance 066
A June 2 press conference, held amid props on stage in the Speech Arts Building, unveiled plans for a major renovation of the John Wright Threatre and support spaces on campus. State construction monies totaling $1.8 million will be supplemented with $425,000 in private gifts, which the university hopes to raise in order to provide a first-rate facility for campus and community. Pictured in front of the press corps are Vinci Ricchiuti '81, chair of the fund-raising effort, President Harold Haak, and Professor Ron Johnson, chair of the Theatre Arts Department. Remodeling work will start this fall, with completion set for the opening of the fall semester, 1990.